# What is the sum of the solutions of 2 |3x − 2| - 6 = −4 ?

*print*Print*list*Cite

### 1 Answer

2 l3x-2l -6 = -4

Move -6 to the right side of the equation by adding 6 to both sides.

2 l3x-2l = 6-4

Subtract 4 from 6 to get 2.

2 l3x-2l = 2

Divide each term in the equation by 2.

2 l3x-2l = 2

______ ___

2 2

Simplify the equation.

l3x-2l = 1

Remove the absolute value by placing a +/- on the right side of the equation.

3x-2 = +/- (1)

Set up the + solution.

3x-2=1

3x=3

x=1

Now set up the - solution.

3x-2 = -1

3x=2-1

3x=1

x= 1/3

**The solution set of the equation is x= 1, 1/3**

**The sum of the solution set is 1 + 1/3 = 1 1/3**